PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MENGGUNAKAN MODEL PROBLEM BASED LEARNING MATA PELAJARAN PENDIDIKAN PANCASILA KELAS II DI SDN 02 TIMPEH - M. Anggrayni; Agus Saputra; Diana (STKIP Subang, 2024)
This research is based on problems in Pancasila education learning, namely that in the ongoing learning process activities, students have difficulty understanding the material and learning outcomes are still low. The teaching materials used are less interesting and the learning atmosphere seems monotonous. This certainly affects student learning outcomes. The aim of this research is to develop